Metal hydride-based hydrogen production and storage system for stationary applications powered by renewable sources - Rangel, C. M. (2022)
ABSTRACT: The development of systems for production and storage of hydrogen as an energy vector for various applications, has gained much relevance in recent years as it is considered critical in the increase of renewable energies in the energy mix. Presently, most part of the hydrogen production using renewable energy sources is based on electrolysis systems that use water to obtain green hydrogen, that can be stored and later used or converted to electrical energy using fuel cells. New laboratory reactor systems for the production and storage of hydrogen using metal hydrides have been demonstrated in recent years, making these kind of reversible electrochemical systems alternative future options for the production and storage of hydrogen.